2020
DOI: 10.1002/per.2267
|View full text |Cite
|
Sign up to set email alerts
|

Becoming More Conscientious or More Open to Experience? Effects of a Two–Week Smartphone–Based Intervention for Personality Change

Abstract: Research indicates that it might be possible to change personality traits through intervention, but this clinical research has primarily focused on changing neuroticism. To date, there are no established, proven techniques for changing other domains of personality, such as conscientiousness and openness. This research examined the effects of a two‐week smartphone‐based intervention to either change one facet of conscientiousness (i.e. self‐discipline) or one facet of openness to experience (i.e. openness to ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 94 publications
3
55
0
1
Order By: Relevance
“…Furthermore, previous intervention studies have often focused on few specific traits people chose to change, such as 'become more open-minded'. The focus on one or two traits may have facilitated successful trait change because of concentrating efforts and resources on single domains (Allan et al, 2018;Hudson et al, 2019;Hudson & Fraley, 2015;Stieger et al, 2020). In previous studies as well as the current one, change goals were moderately correlated, that is, people who wanted to become more sociable often also wanted to become more emotionally stable and conscientious (Hudson & Roberts, 2014).…”
Section: Change Goals Do Not Predict Trait Changes and Momentary Expementioning
confidence: 93%
See 3 more Smart Citations
“…Furthermore, previous intervention studies have often focused on few specific traits people chose to change, such as 'become more open-minded'. The focus on one or two traits may have facilitated successful trait change because of concentrating efforts and resources on single domains (Allan et al, 2018;Hudson et al, 2019;Hudson & Fraley, 2015;Stieger et al, 2020). In previous studies as well as the current one, change goals were moderately correlated, that is, people who wanted to become more sociable often also wanted to become more emotionally stable and conscientious (Hudson & Roberts, 2014).…”
Section: Change Goals Do Not Predict Trait Changes and Momentary Expementioning
confidence: 93%
“…Currently, studies on associations between change goals and actual Big Five trait changes have displayed somewhat mixed results with change goals often, but not always, predicting trait changes in the desired direction (Asadi et al, 2020;Baranski et al, 2020;Hudson et al, 2019;Hudson & Fraley, 2015, 2016aRobinson et al, 2015;Stieger et al, 2020). In these studies, traits were self-reported and trait changes were implemented as differences in self-reports across time.…”
Section: Volitional Personality Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This gap is important because other nonclinical trait-like characteristics (e.g., personality) have shown considerable age differences Soto et al, 2010). These age differences in other traits have led to a proliferation of studies assessing the malleability of psychological characteristics and interventions aimed at improving outcomes for individuals and their significant others (Hudson et al, 2020;Stieger et al, 2020). In the current study, we examined crosssectional age differences in the BAP in a large sample of nearly 3000 adults ranging in age from 18 to 85.…”
Section: Introductionmentioning
confidence: 99%